2022
DOI: 10.4018/ijabim.300349
|View full text |Cite
|
Sign up to set email alerts
|

Influential Factors on Business Operation Sustainability of Entrepreneurs

Abstract: The purpose of his study is to determine the factors that influence the sustainability of entrepreneurial business operations in the Lower Northeastern Area of Thailand, across varies industries. We followed the marketing mix (5P) model exploring product perspective, price perspective, distribution channel, promotion perspective and people perspective and their influence on entrepreneurial business operations sustainability. There was a strong emphasize on the quality and quantity of products provided as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…This is reinforced by FOMO and peer pressure, as the fan may feel that purchase is also necessary to show commitment and loyalty (Kim et al, 2018;Nurani & Sobari, 2022). Findings about the positive influence of fandom involvement and media activity is supported by Suvittawat (2022) because through media posts and comments fans not only inform each other but also recommend idol-related products, thereby increasing peer pressure and fear of missing out.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…This is reinforced by FOMO and peer pressure, as the fan may feel that purchase is also necessary to show commitment and loyalty (Kim et al, 2018;Nurani & Sobari, 2022). Findings about the positive influence of fandom involvement and media activity is supported by Suvittawat (2022) because through media posts and comments fans not only inform each other but also recommend idol-related products, thereby increasing peer pressure and fear of missing out.…”
Section: Discussionmentioning
confidence: 91%
“…Kim et al (2018) also found a positive significant relationship between repurchase intention and the intensity of fandom activities in Korea. Suvittawat (2022) detected characteristics of purchasing of products endorsed by K-pop artists among Thai fans. In the latter study it was also mentioned that fans not only buy these products but also recommend purchases to each other, something which -combined with peer pressure in fandoms -may result high level of purchase intention toward K-pop and K-drama related goods.…”
Section: Purchase Behaviour Of K-pop Fansmentioning
confidence: 99%
See 2 more Smart Citations
“…Endris and Kassegn, (2022) have studied MSMEs in some parts of Africa while Panigrahi and Rao, (2018) have studied the cognition with respect to supply chain processes of Micro, Small and Medium Enterprises in India. Sustainability for MSMEs has been studied in Phillipines Badoc-Gonzales et al, (2021, Thailand (Amornkitvikai et al, 2022Mongkol, 2022;Suvittawat, 2022), Tanzania (Eijdenberg, 2019), Indonesia (Gunawan, & Cahayani, 2022: Purba et al, 2021, Ethopia (Tekola & Gidey, 2019) and Vietnam (Truong, 2022) besides India (Agarwal et al, 2023;Khurana et al, 2019). Fassin et al (2015) has reported the cognition process of Micro, Small and Medium Enterprises owner-managers' from six countries in Europe Keeping Corporate Social Responsibility and sustainability at the core, they report customs, linguistic variable and dissemination of knowledge as factors.…”
Section: Msmes and Sustainabilitymentioning
confidence: 99%